PENGARUH PENGGUNAAN MEDIA INTERAKTIF BERBASIS POWERPOINT TERHADAP PEMAHAMAN KONSEP WAKTU PADA MATA PELAJARAN MATEMATIKA SISWA KELAS II SD UPTD INPRES KUANINO 2 - Usfinit, Skolastika; Margarita Anastasia Hendrik, Hingrida; Bodkova Koli, Radka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low level of students' understanding of time concepts in mathematics learning requires innovative learning media that can present abstract concepts in a more concrete and engaging way. This study aimed to determine the effect of using PowerPoint-based interactive media on second-grade students' understanding of time concepts at SD UPTD Inpres Kuanino 2. The study employed a quantitative approach using a pre-experimental method with a One-Group Pretest–Posttest Design. The participants consisted of 20 second-grade students selected through total sampling. Data were collected using pretest and posttest instruments measuring students' understanding of time concepts. The data were analyzed using descriptive and inferential statistics with the assistance of IBM SPSS Statistics version 22. The findings revealed a significant improvement in students' understanding after the implementation of the interactive media. The mean pretest score increased from 59.50 to 79.15 in the posttest. Furthermore, the standard deviation decreased from 13.465 to 9.235, indicating that students' learning outcomes became more evenly distributed after the treatment. The results demonstrate that PowerPoint-based interactive media has a positive and significant effect on improving students' understanding of time concepts in mathematics learning. Therefore, the use of interactive PowerPoint media is recommended as an innovative instructional medium to enhance students' conceptual understanding and learning engagement in elementary schools.